PENGEMBANGAN BAHAN PEMBELAJARAN BAHASA INGGRIS BERBASIS PCK UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR KRITIS SISWA - Zurnyta (UNIB Press, 2024)
Current learning refers to 21st century learning. One of the characteristics of 21st century learning is critical thinking skills. It can be developed through pedagogical content knowledge (PCK) based learning materials. The purpose of this study is to produce learning materials that integrate the PCK concept through the Anderson and Krathwolh Taxonomy learning path. This development research uses 4D (four-D) development model. The research subjects were students of class XII of SMKN 2 Mukomuko, Bengkulu province. The focus of developing English learning materials are three things, namely the syllabus, learning implementation plans (RPP) and student worksheets (LKPD). The method of data analysis is descriptive qualitative analysis and the type of one group pretest-posttest design which described in the distribution of validator scores and categories of predetermined rating scales. The development of these three learning materials proven to significantly improve students' critical thinking skills. Learning materials based on PCK can be developed continuously and it can also used for different materials